[Ni(cod)2][Al(ORF)4], a Source for Naked Nickel(I) Chemistry. (13th October 2015) - Schwab, Miriam M.; Himmel, Daniel; Kacprzak, Sylwia; Kratzert, Daniel; Radtke, Valentin; Weis, Philippe; Ray, Kallol; Scheidt, Ernst‐Wilhelm; Scherer, Wolfgang; de Bruin, Bas; Weber, Stefan; Krossing, Ingo
Abstract: The straightforward synthesis of the cationic, purely organometallic Ni I salt [Ni(cod)2 ] + [Al(OR F )4 ] − was realized through a reaction between [Ni(cod)2 ] and Ag[Al(OR F )4 ] (cod=1, 5‐cyclooctadiene). Crystal‐structure analysis and EPR, XANES, and cyclic voltammetry studies confirmed the presence of a homoleptic Ni I olefin complex. Weak interactions between the metal center, the ligands, and the anion provide a good starting material for further cationic Ni I complexes. Abstract : Homoleptischer Nickel(I)‐Komplex : Ein lösungsmittelfreier organometallischer Nickel(I)‐Komplex wurde durch die Reaktion von [Ni 0 (cod)2 ] mit Ag[Al(OR F )4 ] (cod=1, 5‐Cyclooctadien, OR F =OC(CF3 )3 ) erhalten. Kristallstrukturanalyse, XANES, EPR‐Spektroskopie und Cyclovoltammetrie bestätigen, dass es sich um [Ni(cod)2 ] + [Al(OR F )4 ] − handelt, welches eine gute Ausgangsverbindung für die Synthese anderer kationischer Nickel(I)‐Komplexe darstellt.